Salinity Management in the Shatt Al-Arab River - Amtair Rahi, Khayyun (International Journal of Engineering and Technology, 2018)
Shatt al-Arab River is originated at the confluence of Tigris and Euphrates in al-Qurna town in southern Iraq. Two other tributaries; the Karun and the Karkheh rivers; join the river downstream from the eastern bank. The length of Shatt al-Arab is about 192 km from its origin to its mouth in the Gulf. The width of the Shatt varies between 250 m at Qurna and 750 m at its mouth at Rass al-Bisha. The salinity of Shat al-Arab has increased steadily for the last four decades. High salinity of the shatt waters hindered their use and made them unfit for most domestic, agricultural and industrial uses. Salinity as high as 18500 ppm was recorded in the City of Basra on the year 2009. Â The prime cause of the salinity problem is the reduction of fresh water inflow from all the contributing rivers; the high salinity of the inflow from the Euphrates; the marshes; and Garmat Ali River. The research paper recommends an environmental (a minimum instream) flow of 145 cms and several engineering works on the lower parts of the Euphrates and the Tigris rivers to assure the delivery of the proposed flow.Â